SISTEM PENDIDIKAN NASIONAL DALAM KAJIAN FILSAFAT PENDIDIKAN MODERN - Taek, Emilia; Bachri, Bacthiar Syaiful; Susarno, Lamijan Hadi Susarno; Dau, Yoseph Lodowik Deki (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2024)
Education is a conscious effort by humans to shape themselves to become quality human beings. This means that education is an important element in life that humans must pursue. The fact that education is an important element means that education must receive special attention from humans themselves. The Indonesian people realize the importance of education. The National Education System is one of the realities found in Indonesia. This system firmly, clearly and systematically regulates all the dynamics of Indonesian education. The existence of the Education System needs to be realized that this system is a legal product. Furthermore, the National Education System is viewed from various perspectives, one of which is the view of modern educational philosophy. Modern educational philosophy seeks to see the extent to which the National Education System exists. The aim of this article is to examine the existence of a national education system within the framework of modern educational philosophy. The research method used is library research. The data collection technique used was to examine all the sources the author obtained in the form of book texts and research journals. The results of the discussion are a study of the National Education System as a legal product. Another result is a study of educational philosophy, the formulation of educational philosophy and the relevance of the modern educational philosophy paradigm to the National Education System. The conclusion displays the unity and logic of the writing.